Microbiological features and clinical impact of the type VI secretion system (T6SS) in Acinetobacter baumannii isolates causing bacteremia. Issue 7 (3rd October 2017) - Kim, Jungok; Lee, Ji-Young; Lee, Haejeong; Choi, Ji Young; Kim, Dae Hun; Wi, Yu Mi; Peck, Kyong Ran; Ko, Kwan Soo
ABSTRACT: We investigated the genetic background and microbiological features of T6SS-positive Acinetobacter baumannii isolates and clinical impact of the T6SS in patients with A. baumannii bacteremia. One hundred and 62 A. baumannii isolates from patients with bacteremia in 2 tertiary-care hospitals in Korea were included in this study. Approximately one-third (51/162, 31.5%) of the A. baumannii clinical isolates possessed the hcp gene, and the hcp -positive isolates were found in several genotypes in multilocus sequence typing. The expression and secretion of Hcp protein varied among the clinical isolates. A. baumannii isolates with detectable Hcp secretion (T6SS+) could better outcompete Escherichia coli compared with T6SS- isolates, including hcp -negative and inactivated hcp -positive isolates. In addition, T6SS+ isolates showed higher biofilm-forming activity and better survival in the presence of normal human serum than the T6SS– isolates. T6SS+ isolates were more frequently detected in patients with catheter-related bloodstream infection, haematopoietic stem cell transplant recipients, and patients receiving immunosuppressive agents. However, T6SS was not a prognostic factor for mortality. Our results suggest that the T6SS of A. baumannii is associated with virulence and contributes to infections in immunocompromised patients and those with implanted medical devices.